Enhancing Consumer Experience at Modern Coffee Shops through Analysis of Customer Acquisition Cost, Lifetime Value, and Implementation of Blockchain Technology: A Case Study in Medan City - Winata, Edi; Ayu, Ade Rahma; Idris, Iswandi (CV. Media Digital Publikasi Indonesia, 2025)
This study explores the influence of Customer Acquisition Cost (CAC), Lifetime Value (LTV), and Blockchain Technology on consumer experience in modern coffee shops in Medan. The research combines quantitative and qualitative approaches, using surveys, interviews, and regression analysis to identify key relationships. The findings indicate a significant positive relationship between CAC, LTV, and consumer satisfaction, showing that optimized acquisition costs and higher customer lifetime value enhance consumer experience. Furthermore, the implementation of Blockchain Technology in these coffee shops has led to increased transparency and trust, further elevating the consumer experience. Coffee shops that adopted blockchain technology showed higher customer loyalty and operational efficiency. These results provide actionable insights for coffee shop owners and stakeholders to improve their marketing strategies and remain competitive in a dynamic market